Pengaruh Fasilitas, Pelayanan dan Koleksi Buku terhadap Minat Baca (Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the effect of library facilities, library services, and book collections on the reading interest of class XI students in the library of SMK Negeri 1 Wonosobo either simultaneously or partially. The population in this study were all students of class XI at SMK Negeri 1 Wonosobo totaling 444 students and a sample of 210 students was taken using proportional random sampling technique. Data were collected by questionnaire. Methods of data analysis using descriptive percentage, multiple regression analysis, hypothesis testing F test and t test. The results showed: 1) there was a simultaneous positive and significant effect between library facilities, library services, and book collections on the reading interest of class XI students in the library of SMK Negeri 1 Wonosobo by 65.2%; 2) There is a positive and partially significant effect between library facilities on reading interest in class XI students in the library of SMK Negeri 1 Wonosobo by 8.41%; 3) There is a positive and partially significant effect between library services on reading interest in class XI students in the library of SMK Negeri 1 Wonosobo by 14.5%; 4) There is a positive and partially significant effect between book collections on reading interest of class XI students in the library of SMK Negeri 1 Wonosobo by 19.36%.